Lisuride for levodopa‐induced complications in Parkinson's disease - Clarke, C E (Cochrane Database Syst Rev, 1999)
BACKGROUND: Long‐term levodopa therapy in Parkinson's disease is associated with the development of motor complications including abnormal involuntary movements and a shortening response to each dose (wearing off phenomenon). It is thought that dopamine agonists can reduce the duration of immobile off periods and the need for levodopa therapy whilst maintaining or improving motor impairments and only minimally increasing dopaminergic adverse events. OBJECTIVES: To compare the efficacy and safety of adjuvant lisuride therapy versus placebo in patients with Parkinson's disease, already established on levodopa and suffering from motor complications. SEARCH METHODS: Electronic searches of MEDLINE, EMBASE and the Cochrane Controlled Trials Register. Handsearching of the neurology literature as part of the Cochrane Movement Disorders Group's strategy. Examination of the reference lists of identified studies and other reviews. Contact with Cambridge Laboratories and Roche Products Limited. SELECTION CRITERIA: Randomised controlled trials of lisuride versus placebo in patients with a clinical diagnosis of idiopathic Parkinson's disease and long‐term complications of levodopa therapy. DATA COLLECTION AND ANALYSIS: Data was to be abstracted independently by each author and differences settled by discussion. MAIN RESULTS: No randomised controlled trials comparing lisuride with placebo in advanced Parkinson's disease with motor complications were found. AUTHORS' CONCLUSIONS: Well designed randomised controlled trials demonstrating efficacy and safety are required before the use of lisuride in later Parkinson's disease can be supported.